2020
DOI: 10.1038/s41598-020-71102-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of racial differences in breast tumor microbiome

Abstract: Studies have demonstrated that environmental, host genetic, and socioeconomic factors influence the breast cancer prevalence landscape with a far-reaching influence on racial disparity to subtypes of breast cancer. To understand whether breast tissue harbors race-specific microbiota, we performed 16S rRNA gene-based sequencing of retrospective tumor and matched normal tissue adjacent to tumor (NAT) samples collected from Black non-Hispanic (BNH) and White non-Hispanic (WNH) women. Analysis of Triple Negative B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 62 publications
(67 reference statements)
4
50
0
Order By: Relevance
“…Similar to what is observed in the skin samples, the breast tissue demonstrates predominance of Proteobacteria and Firmicutes ( Table 1 B.). Reduced Proteobacteria abundance in BD samples is evident in studies comparing HC to BD [ [22] , [23] , [24] , [25] ]. Although subtle differences in Firmicutes abundance between HC and BD samples are observed, no overarching trend in predominance of these organisms can be established at the phyla level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to what is observed in the skin samples, the breast tissue demonstrates predominance of Proteobacteria and Firmicutes ( Table 1 B.). Reduced Proteobacteria abundance in BD samples is evident in studies comparing HC to BD [ [22] , [23] , [24] , [25] ]. Although subtle differences in Firmicutes abundance between HC and BD samples are observed, no overarching trend in predominance of these organisms can be established at the phyla level.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced Proteobacteria abundance in BD samples is evident in studies comparing HC to BD. [22][23][24][25] Although subtle differences in Firmicutes abundance between HC and BD samples are observed, no overarching trend in predominance of these organisms can be established at the phyla level.…”
Section: Phyla Of Healthy and Diseased Breastmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the bacteria associated with breast cancer shared b-glucuronidase activity and, therefore, the authors suggested that this enzymatic activity may promote breast cancer. Recently, two studies described racial differences in the microbiome of breast tumors (Smith et al, 2019;Thyagarajan et al, 2020) while another study identified differences in diversity and composition not only between tumor and normal tissue but also among women and between the breasts of the same woman (Klann et al, 2020).…”
Section: Microbiota Of the Breast Tissue Of Non-lactating Womenmentioning
confidence: 99%
“…Studies have demonstrated that nature environmental, host genetic, and socioeconomic factors influence the breast cancer prevalence landscape with a farreaching influence on racial disparity to subtypes of breast cancer [35]. The socioeconomic effects on the incidence and death of the breast cancer need pay enough attentions, the socio-economic disparities in breast cancer survival prevail even in this relatively homogenous society [36].…”
Section: Introductionmentioning
confidence: 99%